Toward Self-Driving Bicycles Using State-of-the-Art Deep Reinforcement Learning Algorithms - Choi, SeungYoon; Le, Tuyen P.; Nguyen, Quang D.; Layek, Md Abu; Lee, SeungGwan; Chung, TaeChoong (Symmetry (Basel), 2019)
In this paper, we propose a controller for a bicycle using the DDPG (Deep Deterministic Policy Gradient) algorithm, which is a state-of-the-art deep reinforcement learning algorithm. We use a reward function and a deep neural network to build the controller. By using the proposed controller, a bicycle can not only be stably balanced but also travel to any specified location. We confirm that the controller with DDPG shows better performance than the other baselines such as Normalized Advantage Function (NAF) and Proximal Policy Optimization (PPO). For the performance evaluation, we implemented the proposed algorithm in various settings such as fixed and random speed, start location, and destination location.